2005
DOI: 10.1051/forest:2005016
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation partitioning and related nutrient fluxes in a subtropical forest in Okinawa, Japan

Abstract: -Precipitation partitioning into throughfall and stemflow and related hydrochemical fluxes were examined during a 3 y period from January 1998 to December 2000 in a subtropical evergreen broad-leaved forest on Okinawa Island, Japan. Monthly water samples were collected to determine the concentrations and associated fluxes of bioelements. The mean annual precipitation during the study period was 3325 mm. Typhoons played a central role in the hydrology of the study forest with 11 typhoons contributing 29.1% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
3
19
0
1
Order By: Relevance
“…A similar trend of total DOC increment in the sequence from precipitation to throughfall and stemflow observed in the E. grandis plantation was reported for some forests too (Moreno et al 2001, Xu et al 2005. However, the magnitude among fluxes differed significantly, since in the E. grandis plantation DOC concentrations in throughfall and stemflow were 3.2 and 33.4 times respectively higher as those in the precipitation, meanwhile, for example, Xu et al (2005) reported 2.7 and 3.6 times, respectively.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…A similar trend of total DOC increment in the sequence from precipitation to throughfall and stemflow observed in the E. grandis plantation was reported for some forests too (Moreno et al 2001, Xu et al 2005. However, the magnitude among fluxes differed significantly, since in the E. grandis plantation DOC concentrations in throughfall and stemflow were 3.2 and 33.4 times respectively higher as those in the precipitation, meanwhile, for example, Xu et al (2005) reported 2.7 and 3.6 times, respectively.…”
Section: Discussionsupporting
confidence: 50%
“…We employed the available data from a 2-year water balance study of Tesón (2012) for the same plantations and the DOC concentrations of the present study to model the DOC annual circulation. For the periods April -March 2003-2005, we added the products of each water flux measurements per its DOC concentration. For the few sampling intervals without DOC measurements, we employed the significant regressions between DOC concentration and water flux obtained in the present study, or the DOC weighted means for fluxes when regressions were not significant.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, experimental measurements indicated that C. korshinskii had a larger MTA, LAB, LNB and LAI (an average of 54.4 • , 2509.1 cm 2 , 12 479 and 2.4, respectively) and a smaller ILAB (an average of 21.9 mm 2 ) than did S. psammophila (an average of 48.5 • , 1797.9 cm 2 , 2404, 1.7 and 87.5 mm 2 , respectively). The concave leaf shape, upward leaf orientation (MTA) and densely veined leaf structure (ILAB) (Xu et al, 2005) provided stronger leaf structural support in C. korshinskii for the interception and transportation of precipitation, particularly during highly intense rains. Therefore, in addition to the leaf morphology, C. korshinskii was also equipped with more beneficial leaf structural features for stemflow yield.…”
Section: Effects Of Leaf Traits On Stemflow Yieldmentioning
confidence: 99%
“…However, as to biotic mechanisms, although the canopy structure (Mauchamp and Janeau, 1993;Crockford and Richardson, 2000;Pypker et al, 2011) and branch architecture (Herwitz, 1987;Murakami, 2009;Carlyle-Moses and Schooling, 2015) have been studied for years, the most important plant traits vary with location and shrub species and have not yet been determined. The effects of the leaves have been studied more recently at a smaller scale, e.g., leaf orientation (Crockford and Richardson, 2000), shape (Xu et al, 2005), arrangement pattern (Owens et al, 2006), pubescence (Garcia-Estringana et al, 2010), area (Sellin et al, 2012), epidermis microrelief (RothNebelsick et al, 2012), amount , or biomass (Yuan et al, 2016). Comparisons of stemflow yield during summer (the growing or foliated season) and winter (the dormant or defoliated season) generally indicate negative effects of leaves because more stemflow occurs during the leafless period (Dolman, 1987;Masukata et al, 1990;Neal et al, 1993;Mużyło et al, 2012).…”
Section: Yuan Et Al: Comparisons Of Stemflow and Its Bio-/abioticmentioning
confidence: 99%
See 1 more Smart Citation